Platelet-engineered CAR-T cells as adjuvant therapy after cancer surgery - Yixin Wang; Edikan Ogunnaike; Huan Yang; Sichen Yuan; Rachel Hong; Allie Barrett; Emem Ebong; Bo Liu; Gianpietro Dotti; Quanyin Hu (Proceedings of the National Academy of Sciences, 2025)
Surgery remains the mainstay treatment for many kinds of solid tumors, while tumor recurrence frequently occurs. Adjuvant therapy can reduce the risk of recurrence and improve the prognosis of surgery. Chimeric antigen receptor (CAR)-T cell therapy can be leveraged as an alternative adjuvant therapy to clear residual cancer cells and prevent tumor recurrence. However, systemic administration of CAR-T often results in insufficient tumor infiltration and side effects to normal organs. Given that platelets can preferentially accumulate at postsurgical wounds, we proposed that conjugating platelets to CAR-T cells may enhance the accumulation of the CAR-T cells within the surgical bed after the resection of solid tumors. In this study, we conjugated platelets to B7-H3.CAR-T cells via click chemistry. In postsurgical human pancreatic cancer mouse models, platelet-CAR-T cells showed enhanced tumor infiltration and elevated antitumor cytokine levels, resulting in superior suppression effects on tumor recurrence, compared with CAR-T cells. Additionally, platelet-CAR-T cells showed enhanced efficacy in inhibiting metastasis and prolonging the survival time of the mice in postsurgical triple-negative breast cancer (TNBC) models. Mechanistic studies revealed that platelet activation could improve the CAR-T cell activity and persistence, as evidenced by an upregulation of genes associated with T cell infiltration and a downregulation of genes related to T cell exhaustion. Finally, we further validated the biosafety profile and efficacy of platelet-CAR-T in a postsurgical patient-derived xenograft TNBC-bearing humanized mouse model. The results suggested that the CAR-T cell strengthened by platelet engineering is a promising adjuvant therapy against postsurgical tumor recurrence.